The Influence of Diversity on Employee Performance Study Case: PT Tanjung Migas Tanjung Morawa - Robert Sanjaya Sembiring; Pesta Damayanti; Iqbal Agustia Miransyah; Ritha F Dalimunthe (Indonesian Journal of Business Analytics, 2024)
The purpose of this study aims to explain and analyse the effect of diversity on employee performance at PT Tanjung Migas Tanjung Morawa. The data sources in this study are primary data, namely employees of PT Tanjung Migas Tanjung Morawa and secondary data sources as a reference tool, namely journals and some literature and other documents. The population of this research data is all employees of PT Tanjung Migas Tanjung Morawa, totalling 33 people and sampling using a census. then the data collection method uses a questionnaire with SEM Smart PLS software as a data analysis tool. The results showed that there is a positive and significant relationship between diversity and employee performance. Hopefully PT Tanjung Migas can continue to evaluate in improving the application of Diversity to employees through aspects of ethnicity, gender, age, and religion so as to make employees feel comfortable at work in order to provide satisfactory performance for the company.